Decline‐associated Phaeoacremonium species occurring on forest trees in the north of Iran. Issue 6 (29th July 2017) - Kazemzadeh Chakusary, M.; Mohammadi, H.; Khodaparast, S. A.
Summary: Between 2013 and 2015, several surveys were conducted throughout forest areas in the north of Iran with the aim of isolating and identifying fungi present on trees showing decline symptoms. Fungal species, isolated from symptomatic wood tissues of various tree genera, including Zelkova, Acer, Parrotia, Quercus, Diospyros, Fagus, Fraxinus, Populus, Pinus, Pterocarya, Gleditsia, Carpinus, Ulmus, Crataegus, Alnus, Mespilus, Punica, Cydonia, Cupressus and Prunus, were morphologically identified and characterized. A molecular identification based on comparisons of DNA sequences of the β‐tubulin gene allowed us to identify seven species belonging to Phaeoacremonium ; namely, Phaeoacremonium parasiticum, Pm. alvesii, Pm. minimum, Pm. iranianum, Pm. scolyti, Pm .  fraxinopennsylvanicum and Pm. croatiense were isolated and identified . Phaeoacremonium minimum was the most common species and isolated from Gleditsia caspica, Parrotia persica, Cydonia oblonga and Alnus glutinosa . Pathogenicity on selected plants using a mycelium plug inoculation method revealed that most of these species are pathogenic to all the tested trees, with Pm. parasiticum and Pm. minimum being the most pathogenic species. According to host plant species and geographical distribution, the majority of Phaeoacremonium species found represent new records. This is also the first report of Pm. croatiense in Iran and outside Croatia.